Separating the Empirical Wheat From the Pseudoscientific Chaff: A Critical Review of the Literature Surrounding Glyphosate, Dysbiosis and Wheat-Sensitivity - Barnett, Jacqueline A.; Gibson, Deanna L. (Frontiers in Microbiology, 2020)
The prevalence of digestive disorders has increased globally, as countries have adopted a more “Westernized” diet pattern. A Western diet, characterized as high in fat and refined carbohydrates, can also be defined as a product of increased technology and industrialization. Modern farmers rely on agrochemicals to meet the needs of a growing population, and these chemicals have shifted the Western diet’s chemical composition. While the number of individuals choosing to live a wheat-free lifestyle without a celiac disease diagnosis has increased, clinical trials have shown that gluten from wheat is not responsible for causing symptoms in healthy individuals suggesting that something else is inducing symptoms. The herbicide, glyphosate, is applied to wheat crops before harvest to encourage ripening resulting in higher glyphosate residues in commercial wheat products within North America. Glyphosate inhibits the shikimate pathway, a pathway exclusive to plants and bacteria. Glyphosate’s effect on dysbiosis was not considered when making safety recommendations. Here, we evaluate the literature surrounding glyphosate’s effects on the gut microbiome and conclude that glyphosate residues on food could cause dysbiosis, given that opportunistic pathogens are more resistant to glyphosate compared to commensal bacteria. However, research on glyphosate’s effects on the microbiome suffers from numerous methodological weaknesses, and these limitations make it impossible to draw any definitive conclusions regarding glyphosate’s influence on health through alterations in the gut microbiome. In this review, we critically evaluate the evidence currently known and discuss recommendations for future studies.